IBN TAIMIYAH’S VIEW ON GOVERNMENT INTERVENTION IN PRICING - Ali Mujahidin; Rika Pristian Fitri Astuti; Ifa Khoiria Ningrum (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This study is a literature review with the normative approach. To achieve the desired objectives, the authors collected data consisting of primary and secondary data. The data obtained through the previous discussion of some theses, books, websites, supported by guidelines of the Qur’an and Al-Hadith. In gathering the data, the researcher uses the method of a documentary, and with the way the method of indirect observation, by visiting the library in search of data. The result of this research that Ibn Taimiyyah had two views in pricing, the first is valid pricing, second is invalid pricing. And valid pricing can be done by the government to stabilize the economic condition which is called intervention. The goal of intervention is to ensure social justice and prosperity of society. Intervention mechanisms are divided into two, namely direct and indirect. Direct intervention in the form of Al-Hisbah, the character of the institution as a corporate planner, set the market mechanism that is not fair. Besides, in the particular circumstances that required the intervention price, for example when there was war and famine, so all the high-priced goods, or when there was speculation in the market, which requires the seller to sell goods, or when there was speculation in the market, which requires the seller to sell goods with high price levels. While the indirect intervention was implemented in the educational problems and the fulfillment of public facilities such as transport and communication.